STUDI PENGGUNAAN KITOSAN TERHADAP PENURUNAN KADAR AMONIAK PADA LIMBAH CAIR KILANG MINYAK OUTLET IMPOUNDING BASIN (OIB) PERTAMINA RU VI BALONGAN, INDRAMAYU - Utami, Risnita Tri; Sunaryo, Sunaryo; Sedjati, Sri (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Development of industrial activities especially refining oil industry is a sector with large potential as a source of wastewater pollution. Mud waste from crude oil is the final waste from refining processes. Ammonia content of the oil refining industry is found in large quantities. This study was aimed to decrease the concentration of Ammonia used Chitosan. The study was conducted in Technologycal Laboratory of Pertamina RU VI Balongan, Indramayu on March-April 2013. The method used in this study was a completely randomized design with five treatments and three repetitions. Treatments in this study were the differences of Chitosan concentrations, i.e.: A 0,0%, %, B 0,3%, C 0,6%, D 0,9% and E 1,2% with contact time of 30 minutes. ASTM (American Society for Testing Materials), were used to analyze Ammonia concentration. The maximum adsorption of Ammonia in Chitosan solution with a concentration of 0,83% in the amount of 48,79%.